Line Detection Using Arranging Coordinate Point Method - Rumaisa Ramadhani; Arief Syaichu Rohman; Yulyan Wahyu Hadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Line detection system is a system line that canrecognize the line mark painted on the road. This is one of thedigital driver assistance tools that improve driving safety. Thevideo streaming captured using a camera which is installed infront of the vehicle as the input system will detected the line byusing the Arranging Coordinate Point Algorithm. The systemwill provide the correction value of the vehicle distance from thecenter of the road and guide the driver to stay on the track.Based on the experiment result, the system could detect astraight and curved line. The line is well detected by the systemin good condition such as less of noise of the road, good weather,and clear lane line. The system has a computational process0.0625 fps with average error calculation of position from thecenter of the road is 0.0992 m and standard deviation is 0.62448m.